PENINGKATAN KEMANDIRIAN DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN METODE MIND MAPPING DI KELAS V SD SWASTA SETIA BUDI ABADI PERBAUNGAN - Risma Hartati (JURNAL TEMATIK, 2018)
This study aims to determine the increased learning independence and social studies learning outcomes of students by using the mind mapping method in grade 5th of private setia elementary school of Eternal Budi Perbaungan. The type of research used is classroom action research. The results showed that before the implementation of the mind method mapping the learning independence of students was low with an average value of 6.25% which had learning independence. After using the mind mapping method in the first cycle, student learning independence increased with an average value of 46.88% having learning independence. In the second cycle with improvement in action, there was an increase in students' independence of learning with an average score of 87.50% capable of independent learning. This shows that the mind mapping method increases IPS learning independence by 37.25%. Furthermore, before the use of the mind mapping method, student learning outcomes are still under study completeness with an average score of 18.75% who are thoroughly studied. After using the mind mapping method in the first cycle, student learning outcomes increased with an average score of 56.26% thoroughly studied. In the second cycle there was an increase in student learning outcomes with an average learning score of 87.50%. This shows that the mind mapping method increases social studies learning outcomes by 18.09%.